An update on radiation therapy in head and neck cancers - Mazzola, Rosario; Fiorentino, Alba; Ricchetti, Francesco; Gregucci, Fabiana; Corradini, Stefanie; Alongi, Filippo (Expert Review of Anticancer Therapy, 2018)
Introduction: Technological and technical improvements allowed for significant advances in the field of radiation therapy (RT) of head and neck cancer (HNC). Several organ-sparing strategies have been investigated with the objective to decrease acute and long-term adverse effects and, subsequently, to assure a better quality of life in patients affected by HNC. In this context, intensity modulated irradiation and the use of multimodality-imaging could help clinicians to obtain a rapid dose fall off towards surrounding healthy tissues and a better delineation of targets volumes and organs at risk. Areas covered: A literature review was performed with the aim to offer an update on radiation therapy in HNC. Expert commentary: During these last years, radiation oncologists have observed a continuous changing regarding radiation treatment for HNC. The adoption of intensity-modulated RT (IMRT) and the use of multimodality-imaging for tumor volume definition and organs at risk or delineation have improved the clinical outcomes of HNC patients. In the future, a better integration of functional imaging for target volume delineation as well as adaptive delivery strategies will allow to further personalize radiation oncology in HNC. Furthermore, the latest breakthrough technologies, such as magnetic resonance imaging (MRI)-linacs and heavy particles technologies have a great potential to improve treatment-related quality of life in HNC. Future studies are needed to demonstrate the clinical advantages of these new RT technologies in HNC.
CRIS-Team Scopus Importer:2025-10-13
Keywords: chemotherapy; Head and neck cancers; IMRT; radiotherapy; update